Disturbed traditional resource management affects the preservation of the Boran cattle in their original habitat - Homann-Kee Tui, Sabine; Rischkowsky, Barbara A.; Steinbach, J.; Ayalew, W. (2004)
The Ethiopian Boran cattle evolved from the Borana pastoralists’ successful breeding strategiesunder the harsh conditions of arid rangelands. At present two types of this breed are known toexist in the Borana rangelands: the Qorti, or the typical Boran, and the Ayuna, its local variantwith smaller body weight and lesser demands on pasture. This paper illustrates the impact ofexternal interference on the maintenance of the Boran cattle breed in its original habitat. Thetraditional land use system of Borana pastoralists has been based on well-planned consultativeherd movements between functional rangeland categories and on herd management, to ensureavailability of adequate grazing and water all year round. The well-intended artificial waterponds in Dida Hara and other parts of the rangelands opened up the pastures for permanentgrazing and uncontrolled settlement. This has led to reduced mobility of the herds andsubsequent overgrazing in those areas which were formerly only seasonally used. At the sametime, the imposition of ruling on land management from the formal administration hascompromised the merits of indigenous pasture management institutions, exacerbating theproblems of resource use. The Borana pastoralists have adjusted their breeding strategies inresponse to the deteriorated rangelands by favouring the breeding of the Ayuna sub-type at theexpense of the Qorti,. and by increasingly acquiring more camels. Conservation of the typicalEthiopian Boran cattle, or Qorti, would require to secure adequate seasonal grazing and waterresources, which would depend on public policies for the functioning and reinforcement of theindigenous consultative and negotiation processes for community-based management of therangelands and the livestock that depend on them. The Ethiopian Boran cattle evolved from the Borana pastoralists’ successful breeding strategiesunder the harsh conditions of arid rangelands. At present two types of this breed are known toexist in the Borana rangelands: the Qorti, or the typical Boran, and the Ayuna, its local variantwith smaller body weight and lesser demands on pasture. This paper illustrates the impact ofexternal interference on the maintenance of the Boran cattle breed in its original habitat. Thetraditional land use system of Borana pastoralists has been based on well-planned consultativeherd movements between functional rangeland categories and on herd management, to ensureavailability of adequate grazing and water all year round. The well-intended artificial waterponds in Dida Hara and other parts of the rangelands opened up the pastures for permanentgrazing and uncontrolled settlement. This has led to reduced mobility of the herds andsubsequent overgrazing in those areas which were formerly only seasonally used. At the sametime, the imposition of ruling on land management from the formal administration hascompromised the merits of indigenous pasture management institutions, exacerbating theproblems of resource use. The Borana pastoralists have adjusted their breeding strategies inresponse to the deteriorated rangelands by favouring the breeding of the Ayuna sub-type at theexpense of the Qorti,. and by increasingly acquiring more camels. Conservation of the typicalEthiopian Boran cattle, or Qorti, would require to secure adequate seasonal grazing and waterresources, which would depend on public policies for the functioning and reinforcement of theindigenous consultative and negotiation processes for community-based management of therangelands and the livestock that depend on them.